Association between triglyceride-glucose index and worsening renal function in the elderly - Li Lei; Hongbin Liang; Yali Qu; Qianhong Zhong; Qiuxia Zhang; Lei Dai; Junyan Lu; Min Xiao; Zhimeng Zhao; Fengyun Zhou; Yun Li; Guifang Hu; et al. (Frontiers in Nutrition, 2022)
BackgroundTriglyceride-glucose (TyG) index is a simple marker of insulin resistance. However, insufficient data is available on whether the TyG index is associated with worsening renal function (WRF) in the elderly. Therefore, this study was designed to explore the association between the TyG index and WRF based on a community elderly cohort.MethodsIn this study, 7,822 elderly (aged ≥ 65 years) adults from southern China were enrolled and divided into four groups according to the TyG index quartiles. The primary endpoint was incident chronic kidney disease (CKD), defined as incident estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2. Additional endpoints included a decline in eGFR of 30% and 40% during the follow-up period.ResultsDuring the median 2.04 year follow-up period, 1,541 (19.7%) participants developed CKD. After adjusting for confounding factors, multivariable Cox regression models revealed significant associations between TyG index and incident CKD (HR per SD increase, 1.21; 95% CI: 1.14–1.29), a decline in eGFR of 30% (HR per SD increase, 1.38; 95% CI: 1.26–1.50), and decline in eGFR of 40% (HR per SD increase, 1.42; 95% CI: 1.24–1.63). Furthermore, compared with those in Q1, participants in Q4 demonstrated a higher risk of developing CKD (HR, 1.59; 95% CI: 1.35–1.88). These positive associations remained consistent across different subgroup populations.ConclusionOur study suggests a positive and independent association between the TyG index and WRF in the elderly.